Analisa Tegangan Maksimal Cutter Planer pada Mesin Serut (Planer) Bambu Modular dengan Metode Elemen Hingga - Kurniawan, Redho; Hendaryanto, Ignatius Aris; Sugiyanto, Sugiyanto; Krisnaputra, Radhian; Irawati, Inggar Septhia (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
The cutter planer is one of the main components of a bamboo planer which functions to flatten the surface of the bamboo blades. The cutter planer has a problem, namely the maximum stress is not known due to the complexity of the components which is difficult to analyze using the mechanical equation calculation method, so that to overcome this problem a numerical method is used, namely the finite element method. In this study, an analysis was carried out on a cutter planer by comparing the process of cutting bamboo slats with two directions of rotation clockwise (CW) and counterclockwise (CCW). The material used in the cutter planer is HSS and bamboo material with petung bamboo. The results of this study show that the highest maximum stress distribution for the cutter occurs in CCW and the lowest maximum stress distribution for the cutter occurs in CW.